Let $\lambda$ be an integer partition: $\lambda=(\lambda_1\geq\lambda_2\geq\dots\geq0)$. Denote its conjugate partition by $\lambda'$. For example, if $\lambda=(4,3,1)$ then $\lambda'=(3,2,2,1)$.

Recall also the notation for the content of a cell $u=(i,j)$ in a partition is $c_u=j−i$.

I have made the following observation which seems interesting enough to ask here.

QUESTION. Is this true? It might even be known. Is it? Any reference? $$\sum_{i\geq1}\lambda_i^2=\sum_{u\in\lambda}(h_u+c_u).$$

REMARK 1. The above identity implies $$\sum_{i\geq1}(\lambda_i^2+(\lambda_i')^2)=2\sum_{u\in\lambda}h_u.$$

REMARK 2. It also implies that $$\sum_{\lambda\vdash n}\sum_{i\geq1}\lambda_i^2=\sum_{\lambda\vdash n}\sum_{u\in\lambda}h_u.$$


2 Answers 2


Another approach is to notice that $$\sum_{u\in\lambda}h_u=\sum_{u}d_u$$ where $d_u=i+j-1$ for $u=(i,j)$.

Proof: The easiest way to see this is that both sides count the number of pairs $\{(i_1,j_1),(i_2,j_2)\}\in\lambda$ such that either $i_1=i_2$ and $j_1\le j_2$ or $j_1=j_2$ and $i_1\le i_2$.

Using this we have $$\sum_{u\in \lambda}(h_u+c_u)=\sum_{u\in \lambda} (c_u+d_u)=\sum_{(i,j)\in \lambda} (2j-1)=\sum_{i\geq 1}\sum_{j=1}^{\lambda_i}(2j-1)=\sum_{i\geq1} \lambda_i^2$$ which gives us the equality we wanted.

  • $\begingroup$ How to see the right hand side $\sum d_u$ is the number of pairs ... ? $\endgroup$
    – ArB
    Oct 2, 2020 at 12:42
  • 1
    $\begingroup$ @ArB If you fix $u=(i_2,j_2)$ then you will have $d_u$ choices for $(i_1,j_1)$. $\endgroup$ Oct 2, 2020 at 17:44

You can prove this by inductively adding boxes to the outside corners of $\lambda$. It is true for $\lambda=\varnothing$. And when you add box $(i,j)$ as an outside corner, you change the sum $\sum_{i \geq 1} \lambda_i^2$ only in the $i$-term where you increase it by $2j-1$; while the hooks increase by one for the $i-1+j-1$ boxes directly to the left or directly above $(i,j)$, and the new hook length of $(i,j)$ plus the new content of $(i,j)$ gives you a total increase to the RHS of $(i-1+j-1)+(1+j-i)=2j-1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.